Strategi Meningkatkan Kemampuan Membaca pada anak Disleksia Kelas IV di SDN 26 Teluk Bayur Padang - Ulfatmi Hasanah; Anugrah Shazqya; Ahmad Nur Huda; Gusmaneli Gusmaneli (Universitas 45 Surabaya, 2024)
Improving the ability to read early can be done with one of the learning methods, namely the Fernald method. Fernald's method in his learning involves all sensory work including visual, auditory, kinesthetic and tactile which is abbreviated as VAKT. This makes researchers interested in researching this problem. This study uses an experimental research in the form of Single Subject Research (SSR) with an A-B-A design. Data was collected under three conditions, namely baseline (A), intervention (B) and baseline (A2) with 17 meetings with the result that the percentage of children's early reading ability was at 88%. Based on the data from this study, it was concluded that the early reading ability of children with learning difficulties increased after being given treatment using the Fernald method in grade IV SDN 26 Teluk Bayur Padang.